Design And Build An Early Warning System For Health Conditions In Climbers Based On Fuzzy Logic - Ahlul A'raaf Femas Salsabil; Agus Hayatal Falah; Jamaaluddin Jamaaluddin; Indah Sulistiyowati (Universitas Nurul Jadid, 2026)
Mountain climbing is currently being popular with the public, both young people and adults. However, there are still many people who are indifferent to the physiological conditions and environmental conditions that exist on the climb. This study aims to combine these two factors, namely physiological factors and environmental factors as an effort to minimize the occurrence of accidents in climbing activities. Physiological factors, namely oxygen saturation and heart rate, are combined with environmental factors of air pressure, which will later be processed with fuzzy logic consisting of 27 rule bases. The test results on the sensor showed high accuracy with an average value of 98.21% for SpO2, 98.01% for heart rate, and 99.10% for air pressure. At the time of the air pressure value of <750 hPa the system is also capable of giving an alarm as a warning. Fuzzy logic testing is quite effective in determining a climber's health status, where the system consistently assigns a